Effect of Taurine on Cisplatin -Induced Nephrotoxicity and Hepatoxicity in Male Rat - Noruzi M.; Zareh S.; Farrokhi F.; Ghaderi Pakdel F. (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2010)
Background and Objectives: Cisplatin, Platinum co-ordinate complex is a widely used antineaplastic agent for treatment of metastatic tumors. Taurine is an organic acid and an endogenous antioxidant. In this study we investigated the protective effect of taurine as an endogenous antioxidant against cisplatin induced nephrotoxicity and hepatotexicity.Methods: 24 male albino rats (180-220 grams) were divided into 4 groups (n=6): (1): saline-treated group (2): cisplatin-treated group (10mg/kg, ip) (3): group that received taurine (400mg/kg, ip) 1hr before cisplatin (10mg/kg, ip) administration (4): taurine (400mg/kg, ip). The animals were killed 7days after treatment and then blood samples were collected.Results: The results of this study indicated that cisplatin significantly increased CRATININ, URE, ALT, AST levels as compared to control group. Moreover, taurine significantly decreased CRATININ, URE, ALT and AST levels compared to cisplatin group.Conclusion: According to this study taurine prevents the incease of Creatinin, BUN, ALT and AST levels assisted by cisplatin, which may be due to its antioxidant properties.Keywords: Cisplatin; Taurine; Hepatoxicity; Nephrotoxicity; Nephrons.